'Going green'! Exploring customer preference in the hotel industry. (1st January 2011) - James, Matrecia S.L.; Miles, Angela K.; Nelson, Millicent F.; Sledge, Sally; Colakoglu, Sidika
Green management has become a new mandate for firms in all industries to use in their operational strategies. The hotel industry has long utilised environmentally friendly practises yet it has incorporated more actions in recent years due to consumer demand. This work offers an exploratory qualitative study of consumer perceptions about the importance of green management practises in purchase decisions for hotel stays. The sample includes hotel customers. Results suggest that green management practises do matter to a majority of customers. Other findings and directions for future research are included.